Periodontal Health Status in a Cohort of Young US Navy Personnel - Kim E. Diefenderfer, DMD, MS, MS, Captain, Dental Corps, US Navy; Renee L. Ahlf, RDH, MSEd; (Blackwell Synergy, 2007)
Neither the prevalence of periodontal disease nor long-term trends in periodontal health among US military personnel has been well studied